THE EKSISTENSI PENERAPAN SISTEM MANAJEMEN PENDIDIKAN TINGGI BERDASARKAN SNI ISO 21001:2018 - Muhammad Yaasiin Raya; Taufiq Hidayat; Yuspiani; Ade Darmawan Basri (Idaarah: Jurnal Manajemen Pendidikan, 2022)
Universities can implemented SNI ISO 21001:2018 as a reference in managing education service system that refers to international education standards. This type of research is qualitative research which is a descriptive type. The object of this research consists of universities that will and have implemented SNI ISO 21001:2018. The subject is National Standardization Agency of Indonesia as the guide institution for implementation of SNI ISO 21001:2018 in universities. Data collection techniques in this study use library research, observation, interviews , and documentation, then analyzed descriptively qualitatively, observation techniques by collecting data through observations of the situation and condition of universities that are currently implementing SNI ISO 21001:2018. The results of this study are: the management system of educational organizations based on SNI ISO 21001:2018 is a management method for providers of educational products and services which are able to fulfill the students requirements and other beneficiaries also can be applied to other organizations that use educational curriculum to support competency development through teaching, learning and research. Implementation of SNI ISO 21001:2018 strength with five main concepts that form the basis for all ISO standard management systems. The five main concepts include risk-based thinking, process approach, plan-do-check-act cycle, management principles, and high-level structure. The stages of the process for implementing SNI ISO 21001:2018 are initial identification condition, system setup, implementation, internal audit, application for certification, assistance for corrective actions and publishing SNI ISO 21001:2018 certificates.